The Agreement for Temporary Service of a Diocesan Priest Outside His Diocese of Incardination According to Canon 271 of the 1983 Code of Canon Law - Obel, Andrew Kinarah (Université Saint-Paul / Saint Paul University, 2017)
Canon 271, §1 of the CIC calls for an agreement between the bishops a quo and ad quem for the temporary service of diocesan clerics outside their dioceses of incardination. The purpose of the agreement is to determine and safeguard the rights and duties of the priests and bishops involved. A 1980 document of the Congregation for the Clergy, Postquam apostoli provides some of the juridical elements that should constitute the content of such an agreement. This thesis is an in-depth study and investigation of the agreement with the aim of contributing additional canonical elements that need to be included in it to make it reflect the current situation faced by the priests and bishops involved. To provide the context under which the written agreement originated, the thesis, in its first chapter, traces the history of the law on the movement of clerics from one diocese to another beginning from the early church period up to the CIC. It examines the various juridic norms that existed before the CIC and observes that throughout its history, the Church has regulated the ministry and movement of clerics by formulating stringent laws that forbade clerics from moving unnecessarily. In the second chapter, the thesis examines the current law on the temporary service of diocesan clerics outside their dioceses of incardination as stipulated in CIC, c. 271. This analysis includes tracing the textual development of the canon and critical analysis of its components. Chapter three carefully discusses the canonical elements that need to be included in the written agreement, and investigates the contractual, binding and obligatory nature of the agreement. It concludes that the agreement (conventio), although not explicitly called a contract (contractus), binds the parties involved, and diocesan bishops are obligated to enter it when they welcome foreign clerics to minister in their dioceses. The fourth chapter is dedicated to the discussion of the drafting process and implementation of the agreement. It analyses eight sample agreements from selected dioceses in Canada, the United States of America and Uganda and highlights the need of drafting the agreement accurately in conformity with the provisions of CIC, c. 271 and the pertinent norms of Postquam apostoli. The analysis of the sample agreements further adds a practical dimension to the thesis and provides examples that other dioceses can use for drafting their own agreements.
Keywords: Agreement; Temporary; Service; Priest